Incentivized Urbanization in Philadelphia: The Local Politics of Globalized Zones. Issue 3 (3rd July 2019) - Wiig, Alan
ABSTRACT: Today, establishing zones for globally-oriented free enterprise is a common strategy of post-industrial urban revitalization and economic development. These large-scale projects typically operate through neoliberal governance and planning that facilitates undemocratic control and privatized administration of the zones. With a case study of the Philadelphia Navy Yard, this paper argues that these spaces embody a "non-plan" of competitive capitalist urbanization governed by and for global firms. However, the present-absence of municipal and state-level oversight itself represents a political decision, to provide place-based incentives without then managing this process. The Navy Yard allowed an unelected public–private partnership to determine how to best use the space, while also offering significant, publicly funded tax subsidies. Although lauded as "successful" by city politicians, the Navy Yard's publicly-funded private benefit did little to reduce longstanding divides in the city, furthering a new era of spatial and political fragmentation.